Intensidades de pastejo e mecanismos sulcadores sobre o desenvolvimento do milho no sistema de integração lavoura-pecuária - Franchin, Marcia Fernanda (2011)
Grazing intensity in no-till areas influences the yield of the crop-livestock system both positively or negatively. Furthermore, these effects can be mitigated by the use of notill seed planter equipped with different drills which can interact in favor of the crops optimizing its productivity. Thus, this study aimed to evaluate different grazing intensities and the influence of seed drills on the development of the corn crop in integrated crop-livestock. The experiment was laid out as random block design in a split-plot design with four replications. Main plots refer to the grazing intensities (ungrazed, 35 x 15, 30 x 10 and 25 x 5 cm of height respectively to the entrance and exit of the animal from the paddocks) and the subplots, the seed drills (double disc and knife). To adjust the wanted forage heights were used dairy cows with average live weight of 500 kg with an intermittent grazing. Real pasture heights of entrance and exit of animals from pasture differed among all grazing intensities. Soil traits were evaluated before and after the grazing period (96 days). After the corn sowing, to evaluate the influence of different grazing intensities and seed drills, the following parameters were assessed: depth of seed deposition, soil area mobilized, rate of emergence, stem diameter, height of plants and height of first ear, yield components and productivity. According to the results, it can be concluded that: Forage accumulation rate showed values of 56.75, 41.9, 41.31 and 32.74 kg of MS ha-1 d-1, and total production was of 7,548, 5.531, 5,494 and 4,322 kg ha-1 of DM respectively for the ungrazed treatment, 35 x 15, 30 x 10 and 25 x 05 cm. Grazing intensities affected the soil density. The area of mobilized soil and seeding depth differed between seed drills being higher to the knife drill. Corn grain yield dynamics were affected by the grazing intensities and seed drills. Corn yield decreased as the grazing intensities increased to the double disc seed drill mechanism with a difference of 942 kg ha-1 between the treatments without grazing and the highest grazing intensity (25 x 5 cm). The use of knife seed drill reduced this difference to 324 kg ha-1, however, this treatment (25 x 5 cm) showed lower productivity than the other grazing intensities, confirming the negative effect of high grazing intensities over the soil density and forage and crops yield.